Tooth surface temperature and power transmission efficiency of plastic sine-curve gear - Takao KOIDE; Tatsuya YUKAWA; Suguru TAKAMI; Akio UEDA; Ichiro MORIWAKI; Atsutaka TAMURA; Junichi HONGU (Journal of Advanced Mechanical Design, Systems, and Manufacturing, 2017)
The present paper describes the tooth surface temperature and the power transmission efficiency of plastic sinecurve gears in the running condition. The plastic sine-curve and involute gears were manufactured by injection molding. The running tests for sine-curve and involute gears were performed under no-lubrication and grease-lubrication conditions, and the tooth surface temperature and the power transmission efficiency were measured. Test results show that the sine-curve gears for operating condition had lower tooth surface temperatures and higher power transmission efficiencies than involute gears under no-lubrication conditions, but in the grease-lubrication condition the superiority of sine-curve gears was not observed.